Activation of a hybrid twinning mechanism in a Cr-Ni-Si-V-N medium manganese austenitic steel containing precipitates. (February 2021) - Shyamal, S.; Farahani, M. Ghiasabadi; Allam, T.; Hamada, A.S.; Haase, C.; Kömi, J.I.; Chakraborti, P.C.; Sahu, P.
Abstract: Twinning nucleation in a medium Mn austenitic steel containing precipitates is studied at low strain ~ 0.02, using transmission electron microscopy. In the near vicinity of the precipitates, unfaulting dislocation reaction is favored, while twinning is activated farther from the precipitates. Twin nucleation follows a hybrid mechanism, involving creation of stacking faults through classical dislocation dissociation, while those stacking faults subsequently overlapped following a non-classical alternated stacking fault pair mechanism to create a three-layer twin nucleus. The observed twinning behavior is interpreted from an energy barrier variation viewpoint within the matrix. Graphical abstract: Image, graphical abstract